ANALYSIS STRATEGY OF SUPPLY CHAIN AT THIRD PARTY LOGISTICS WAREHOUSE FOR DISTRIBUTION PROCESS - Sulistya Pribadi; Rahadian Kafi M; Andri Primadi (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2017)
Research objective is to determine the strategy supply chain that focuses on storage and distribution, as the company acts as a third party logistics, using SWOT Analysis. Through tabulation IFAS and EFAS later to view the results using the Analysis Diagram 4-K that it produces results IFAS  (score 0.79) and EFAS (score -0.31) which produces Supporting Strategies Turn-around. So, the overall total could be seen from the Matrix Internal external is from Internal yield of 3.91 points and 2.46 of external. It means, the company can focus on stability, and the latter using SWOT Matrix (TOWS) to see the position of company that can take one of several possible strategies and company getting WO (weakness and opportunity). Its means, the company should be able to reduce weaknesses in the company in order to take advantage of opportunities that could advance the company.